Numerical Experiments on Oxygen Soft X-Ray Emissions from Low Energy Plasma Focus Using Lee Model - Akel, M.; Al-Hawat, Sh.; Saw, S. H.; Lee, S. (Springer US, 2010)
The X-ray emission properties of oxygen plasmas are numerically investigated using corona plasma equilibrium model. The Lee model is here modified to include oxygen in addition to other gases. It is then applied to characterize the Rico Plasma Focus (1 kJ), finding a oxygen soft X-ray yield (Ysxr) of 0.04 mJ in its typical operation. Keeping the bank parameters and operational voltage unchanged but systematically changing other parameters, numerical experiments were performed finding the optimum combination of pressure = 3 Torr, anode length = 1.5 cm and anode radius = 1.29 cm. The optimum Ysxr was 43 mJ. Thus we expect to increase the oxygen Ysxr of PF-1 kJ thousand-fold from its present typical operation; without changing the capacitor bank, merely by changing the electrode configuration and operating pressure. The modified version of the Lee model code is also used to run numerical experiments with oxygen gas, for optimizing the oxygen soft X-ray yield on the new plasma focus device PF-SY2 (2.8 kJ). The static inductance L0 of the capacitor bank is progressively reduced to assess the effect on pinch current Ipinch. The experiments confirm the Ipinch, limitation effect in plasma focus, where there is an optimum L0 below which although the peak total current, Ipeak, continues to increase progressively with progressively reduced inductance L0, the Ipinch and consequently the soft X-ray yield, Ysxr, of that plasma focus would not increase, but instead decreases. The obtained results indicate that reducing the present L0 of the PF-SY2 device will increase the oxygen soft X-ray yield till the maximum value after that the Ysxr will decrease with Ipinch decreasing.